Incidences and Determinants of Functional Cure During Entecavir or Tenofovir Disoproxil Fumarate for Chronic Hepatitis B. (17th May 2021) - Hsu, Yao-Chun; Yeh, Ming-Lun; Wong, Grace Lai-Hung; Chen, Chien-Hung; Peng, Cheng-Yuan; Buti, Maria; Enomoto, Masaru; Xie, Qing; Trinh, Huy; Preda, Carmen; Liu, Li; Cheung, Ka-Shing; et al.
Abstract: Background: Long-term incidences and baseline determinants of functional cure (hepatitis B surface antigen [HBsAg] seroclearance) during entecavir (ETV) or tenofovir disoproxil fumarate (TDF) treatment are incompletely understood. Methods: This is an international multicenter cohort study of treatment-naive patients with chronic hepatitis B who started ETV or TDF treatment without baseline cancer. Patients were observed for HBsAg seroclearance until death or loss to follow-up. We calculated the incidences and explored the baseline determinants of HBsAg seroclearance using competing risk regression. Results: The analysis included 4769 patients (median age, 50 years; 69.05% male), with a median follow-up of 5.16 years (26 614.47 person-years). HBsAg clearance occurred in 58 patients, yielding a 10-year cumulative incidence of 2.11% (95% confidence interval, 1.54%–2.88%) and an annual rate of 0.22% (.17%–.28%). Baseline predictors included low-level viremia with hepatitis B virus DNA <2000 IU/mL (adjusted subdistribution hazard ratio, 3.14 [95% confidence interval, 1.80–5.49]), elevated serum alanine aminotransferase >200 U/L (3.68 [2.07–6.53]), serum bilirubin (1.11 per mg/dL; [1.06–1.17 mg/dL]), and fatty liver (1.84 [1.03–3.29]). Conclusion: HBsAg seroclearance rarely occurs in patients with chronic hepatitis B treated with ETV or TDF and is associated with low-level viremia, alanine aminotransferase flare, bilirubin level, and fatty liver. Functional cure of hepatitis B virus infection rarely occurred at an average annual rate of 0.22% during first-line oral antiviral treatment, with higher chances observed in patients with low-level viremia, high-level aminotransferase flare, elevation of serum bilirubin, and fatty liver.